Long-term assessment of prostaglandin analogs and timolol fixed combinations vs prostaglandin analogs monotherapy - Liu, Ai-Wei (Int J Ophthalmol, 2016)
AIM: To draw a Meta-analysis over the comparison of the intraocular pressure (IOP)-lowering efficacy and safety between the commonly used fixed-combinations of prostaglandin analogs and 0.5% timolol with prostaglandin analogs (PGAs) monotherapy. METHODS: After searching the published reports from MEDLINE, EMBASE, the Cochrane Library, all randomized controlled clinical trials (RCTs) comparing the fixed combination of PGAs/timolol therapy (FCs) and PGAs monotherapy with treatment duration at least 6mo were included. The efficacy outcomes were mean diurnal IOP, percentage of participants whose IOP were lower than 18 mm Hg, incidence of visual field change, while the safety outcomes included corneal side effects, hyperemia and eye irritation. The analysis was carried out in RevMan version 5.3 software. RESULTS: After six-month medical intervention, the mean diurnal IOP of FCs was lower than PGAs (MD -1.14, 95% CI -1.82 to -0.46, P=0.001); the percentage of target IOP achieving between FCs and PGAs showed no significant difference (RR 1.18, 95% CI 0.97 to 1.43, P=0.10). No statistically significant differences of the incidence of hyperemia (RR 0.67, 95% CI 0.45 to 1.01, P=0.06) and eye irritation (RR 1.20, 95% CI 0.95 to 1.51, P=0.12) between the FCs and PGAs monotherapy were detected. Only one research involved in corneal events, result of this trial revealed no difference between two intervention groups regarding corneal effects (central endothelial cell density, MD -0.20, 95% CI -0.72 to 0.32, P=0.45; central corneal thickness, MD -0.01, 95% CI -0.02 to 0.00, P=0.23). The evaluation of visual field change was not performed due to the limited duration of the trials included in this Meta-analysis. CONCLUSION: The long-term efficacy of the FCs overweighed the PGAs monotherapy in lowering IOP, but in the incidence of hyperemia and eye irritation syndromes, the differences are not statically significant. More RCTs with detailed and authentic data over the assessments of visual functions and morphology of optic nerve heads are hoped to be conducted.